La gestión de la comunicación institucional en la Dirección Zonal 3 de Salud durante la pandemia, periodo enero-junio 2021. - Hidalgo Rosero, Leonardo David (2023)
The current research aims the analysis of the management of communication in the Zonal Health Directorate 3 of Chimborazo, within Covid-19 pandemic; understanding that institutional communication translates identity into an image that is a strategic tool that promotes an adequate positioning, in this case, in the city of Riobamba, it can be determined that the advent of the virus greatly affected the whole world and especially in the communicational aspect. The health area was undoubtedly one of the most affected, not only due to the fact that people's lives were lost on a daily basis and the number of casualties was alarming, but also because health professionals had to deal with serious psychological conditions, hence, the communicative activity enters, since it was sought to provide sufficient and adequate information to the citizenry so that in some way they can remain calm. It is evident that, as established in the results of the surveys applied and the interview with the competent authority, communication was handled in the best way, however, this does not mean that it was optimal, which is why the This research proposal includes a manual for communication management during a health crisis, which will constitute a contribution to the development of different institutions, if possible, at the national level.